Special Considerations in Human Airway Management - Shallik, Nabil A. (IntechOpen, 2021)
In the past three decades, the field of airway management has made significant progress. Airway management is the backbone of anesthesiology, and we have a responsibility to disseminate the most up-to-date information to our colleagues on the front lines and in all disciplines that deal with airway management. It is essential that clinicians become familiar with the most recent developments in equipment and scientific knowledge to allow the safe practice of airway management. As such, this book provides the latest updates on airway management in particular circumstances and highlights recent advances in evidence-based airway management.